New European socio-economic scenarios for climate change research: operationalising concepts to extend the shared socio-economic pathways - Kok, Kasper; Pedde, Simona; Gramberger, Marc; Harrison, Paula A.; Holman, Ian P. (Springer, 2018)
Scenarios have been recognised as a useful tool for planning, which have resulted in a strong increase in the number of (multi-scale) scenarios in climate change research. This paper addresses the need for methodological progress and testing of conceptual considerations, by extending the global shared socio-economic pathways (SSPs). We present a set of four European SSPs until 2100 and a novel method to develop qualitative stories for Europe equivalent to the global SSPs starting from an existing set of European scenarios. Similar to the global SSPs, the set includes a sustainable future with global cooperation and less intensive lifestyles (We are the World; Eur-SSP1); a future in which countries struggle to maintain living standards in a high-carbon intensive Europe (Icarus; Eur-SSP3); a world in which power becomes concentrated in a small elite and where Europe becomes an important player (Riders on the Storm; Eur-SSP4); and one where a lack of environmental concern leads to the over-exploitation of fossil fuel resources addressed by technological solutions (Fossil-fuelled Development; Eur-SSP5). We conclude that the global SSPs are a good starting point for developing equivalent continental scale scenarios that, in turn, can serve multiple purposes. There are, however, methodological challenges related to the choice for equivalence and the exact methods by which scenarios are constructed that need to be tested further.
Keywords: Shared socio-economic pathways; Socio-economic scenario; Multi-scale; Europe; Narratives